The Effect of Accounting Conservatism and Financial Distress on Tax Avoidance With Executive Characteristics as Moderating Variables: Empirical Study on Manufacturing Companies in The Food and Beverage Sub-Sector Listed on the IDX in 2019-2021 - Purwanti; Purnamasari, Atika (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To analyze the effect of accounting conservatism and financial distress on tax avoidance with executive characteristics as a moderating variable. Background Problems: The government wants to continue to increase state revenues through taxes to finance government administration while for corporate taxpayers in this case, namely tax companies. Novelty: Adding moderating variables to the test and using eviews as an analysis tool. Research Methods: This is a quantitative study with a total of 39 companies determined by purposive sampling technique and using eviews as an analysis tool. Findings/Results: The variables of accounting conservatism and financial distress, both partially and simultaneously, do not have a significant effect on tax avoidance. The variable of accounting conservatism does not have a significant effect in moderating and strengthening the relationship with tax avoidance which is moderated by executive character. The variable of financial distress has a significant effect in moderating and strengthening the relationship with tax avoidance which is moderated by executive character. Conclusion: In an effort to reduce the amount of tax avoidance, the government should review the tax legislation policy with events in the field.